Breaking the Silence on Spiritual Abuse - Oakley, L. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Providing a balance of empirical research and practical concerns, this book explores the definitions and historical context of spiritual abuse, outlines a process model for the different stages of spiritual abuse and includes strategies for therapists working with survivors of spiritual abuse.